2013
DOI: 10.1016/j.ultsonch.2012.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Creaming enhancement in a liter scale ultrasonic reactor at selected transducer configurations and frequencies

Abstract: Recent research has shown that high frequency ultrasound (0.4-3 MHz), can enhance milkfat separation in small scale systems able to treat only a few milliliters of sample. In this work, the effect of ultrasonic standing waves on milkfat creaming was studied in a 6L reactor and the influence of different frequencies and transducer configurations in direct contact with the fluid was investigated. A recombined coarse milk emulsion with fat globules stained with oil-red-O dye was selected for the separation trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 21 publications
1
49
0
Order By: Relevance
“…The particle size distribution and the associated volume weighted mean diameter, D [4,3], was determined for all samples before and after processing by ultrasound using a Malvern Mastersizer 2000 (Malvern Instruments Ltd., Worcestershire) with deionised water as the dilutant. Further details of the analysis can be found in Leong et al [4].…”
Section: Sample Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The particle size distribution and the associated volume weighted mean diameter, D [4,3], was determined for all samples before and after processing by ultrasound using a Malvern Mastersizer 2000 (Malvern Instruments Ltd., Worcestershire) with deionised water as the dilutant. Further details of the analysis can be found in Leong et al [4].…”
Section: Sample Characterizationmentioning
confidence: 99%
“…Further details of the analysis can be found in Leong et al [4]. The D [4,3] value represents the mean particle size of the samples, weighted by the total volume of the fat droplets. The purpose of this measurement was to provide an indication of the selectivity of ultrasound under different conditions (frequency and temperature) to manipulate different sized fat globules in a sample of natural whole milk to the fat enriched top or fat depleted bottoms.…”
Section: Sample Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Juliano et al [56] demonstrated the concept of ultrasonic separation for natural whole milk in small test tubes of 7-mL volume and was later successful in scaling this process up to 6 L using a recombined milk emulsion [57]. Leong et al [69] established suitable ultrasonic parameters that enable successful separation of natural whole milk in large scale, demonstrating the importance of energy density and effectiveness of high-frequency ultrasound (1 and 2 MHz) to separate the small fat globules distributed in milk (*4 lm diameter).…”
Section: Ultrasonic Separation Of Fatmentioning
confidence: 99%